Exploring Halal food preferences across age and gender - Md Sawari, Siti Salwa; Abd Rahman, Nur Hidayah; Paramboor, Jaafar; Ghazali, Mohd Al'Ikhsan (EDUSAGE Network, 2018)
It is imperative, based on the religious restriction that Muslims should practically choose halal food as the only dietary lifestyle. This paper aims to investigate the gender and age differences in halal food consumption. Employing a quantitative research design, a total of 730 survey questionnaires was administered to sample population in Peninsular Malaysia. The samples were selected using stratified random sample technique. All participants were required to answer survey questionnaires related to their profile and attitude towards halal food. The result of this study shows that the majority of Muslims in Malaysia have high-level awareness in consuming halal food. For demographic characteristics focusing on the gender, a significant difference was found (p < 0.05). This research also identified that there was no significant difference in respondents’ attitude towards halal food consumption based on age (p > 0.05). The practical implication is specifically for the halal food industry as they would be able to promote the halal culture referring to the findings of this particular study.